Isolation and characterization of gram negative bacteria that may cause UTI from student toilets in UiTM Kuala Pilah / Nooradila Anzeli - Anzeli, Nooradila (2017)
In general, most of gram negative bacteria known as pathogenic and may spread due to the lack hygiene of the toilet. This problem can develop into serious illness like urinary tract infection (UTI). By using a sterile cotton swab, swabbing method was performed to swab different part of the toilet surface include of bowl, floor and seat. Samples were inoculated first on Nutrient agar before re-inoculated on MacConkey and Blood agar. All the samples were incubated at 37oC for 24 hours. Biochemical tests such as catalase, oxidase, IMViC and TSI proceed for bacterial identification. Results showed gram negative bacteria which are E.coli, Pseudomonas spp. and Klebsiella spp. were isolated from the students’ toilets. The result of this study indicates high presence of gram negative bacteria on students’ toilet in UiTM Kuala Pilah.